Exploiting a new strategy to induce immunogenic cell death to improve dendritic cell-based vaccines for lymphoma immunotherapy. (2nd November 2017) - Montico, B.; Lapenta, C.; Ravo, M.; Martorelli, D.; Muraro, E.; Zeng, B.; Comaro, E.; Spada, M.; Donati, S.; Santini, S. M.; Tarallo, R.; Giurato, G.; et al.
ABSTRACT: Although promising, the clinical benefit provided by dendritic cell (DC)-based vaccines is still limited and the choice of the optimal antigen formulation is still an unresolved issue. We have developed a new DC-based vaccination protocol for aggressive and/or refractory lymphomas which combines the unique features of interferon-conditioned DC (IFN-DC) with highly immunogenic tumor cell lysates (TCL) obtained from lymphoma cells undergoing immunogenic cell death. We show that treatment of mantle cell lymphoma (MCL) and diffuse large B-cell lymphoma (DLBCL) cell lines with 9- cis -retinoic acid and IFNα (RA/IFNα) induces early membrane exposure of Calreticulin, HSP70 and 90 together with CD47 down-regulation and enhanced HMGB1 secretion. Consistently, RA/IFNα-treated apoptotic cells and -TCLs were more efficiently phagocytosed by DCs compared to controls. Notably, cytotoxic T cells (CTLs) generated with autologous DCs pulsed with RA/IFNα-TCLs more efficiently recognized and specifically lysed MCL or DLBCL cells or targets loaded with several HLA-A*0201 cyclin D1 or HLA-B*0801 survivin epitopes. These cultures also showed an expansion of Th1 and Th17 cells and an increased Th17/Treg ratio. Moreover, DCs loaded with RA/IFNα-TCLs showed enhanced functional maturation and activation. NOD/SCID mice reconstituted with human peripheral blood lymphocytes and vaccinated with autologous RA/IFNα-TCL loaded-IFN-DCs showed lymphoma-specific T-cell responses and a significant decrease in tumor growth with respect to mice treated with IFN-DC unpulsed or loaded with untreated TCLs. This study demonstrates the feasibility and efficacy of the use of RA/IFNα to generate a highly immunogenic TCL as a suitable tumor antigen formulation for the development of effective anticancer DC-based vaccines.